Empirical study of savings through life insurance in the Republic of Serbia - Lukić, Marija; Piljan, Tatjana; Muhović, Almir (Anali Ekonomskog fakulteta u Subotici, 2021)
Life is a natural course, full of uncertainty and temptation of every human being. In order to make our lives more peaceful and have a more peaceful future, we are trying in various ways to secure ourselves and make our lives safer. Savings through insurance is a life-saving type of savings that involves the material protection of an individual against the risk of premature death and loss or loss of ability to earn money. In conditions where the solidarity-based pension system is unsustainable, it is necessary to develop voluntary pension insurance and savings through life insurance, as sources of long-term savings and additional sources of financing. The subject of this research is to answer the question of what people think about saving through life insurance. The main objective of this research is to evaluate the attitude of the residents of the Republic of Serbia towards saving through life insurance. The survey was conducted on the territory of the entire Republic of Serbia, on a suitable sample of 500 respondents. Through this paper, the citizens’ attitude towards saving through life insurance in the Republic of Serbia is analyzed in one place. By analyzing the data from the survey, we can conclude that the general hypothesis is confirmed: Residents are not satisfied with the current state of savings through life insurance in the Republic of Serbia.